Primer on the metabolic bone diseases and disorders of mineral metabolism - Rosen, Clifford J.; Bouillon, R.; Compston, Juliet; Rosen, Vicki (Ames, Iowa : Wiley-Blackwell, 2013)
Primer on the Metabolic Bone Diseases and Disorders of Mineral Metabolism, 8th Edition is the comprehensive revision of the field-leading reference on bone and mineral health. The eighth edition has been fully revised by the leading researchers and clinicians in the field to provide concise coverage of the widest possible spectrum of metabolic bone diseases and disorders of mineral metabolism. Chapters look to explain basic biological factors of healthy development and disease states and make it easily translatable to clinical interventions.
Nanocomputed Tomography; Imaging Considerations; Voxel size and image resolution; Segmentation; Skeletal site and volume of interest; Calibration; Other considerations; Conclusions; References; 8: Animal Models: Genetic Manipulation; Introduction; Overexpression of Target Genes; Chondrocytes; Osteoblasts; Tendon and ligament; Osteoclasts; Advantages and disadvantages of overexpression approaches; Gene Targeting; Advantages and disadvantages of gene targeting; Tissue-Specific and Inducible Knockout and Overexpression; Uncondensed mesenchyme, mesenchymal condensations, and neural crest; Cartilage; Osteoblasts.
Includes bibliographical references at the end of each chapters and index.
Print version record.
Keywords: Bones -- Metabolism -- Disorders; Mineral metabolism -- Disorders; Bones -- Diseases; Bone Diseases, Metabolic; Bone and Bones -- metabolism; Minerals -- metabolism; HEALTH & FITNESS -- Diseases -- Musculoskeletal; MEDICAL -- Orthopedics; MEDICAL -- Rheumatology; Bones -- Diseases; Bones -- Metabolism -- Disorders; Mineral metabolism -- Disorders; Electronic books